Soil testing - Ambler, Kate; Bloem, Jeffrey R.; McNamara, Brian (International Food Policy Research Institute, 2025)
Soil tests provide farmers with information about the nutrient needs of the soil on their agricultural plots and can help farmers apply the optimal amount and type of fertilizer. Too little fertilizer can stunt plant growth and degrade the quality of soil. Conversely, too much fertilizer can become toxic to plants and generate environmental damage via chemicals leaching into nearby water sources or dissipating into the atmosphere. Applying the wrong type of fertilizer will fail to meet the nutrient needs of crops.